2019
DOI: 10.1159/000499336
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor Effects of Chrysophanol in Malignant Optic Nerve Meningioma Cell Lines are Mediated via Caspase Activation, Induction of Mitochondrial Mediated Apoptosis, Mitochondrial Membrane Depolarization and Targeting the Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: Background: Anthroquinones are considered remarkable anticancer agents. Chrysophanol is an important anthroquinone and it has shown to have the potential to inhibit the growth of the range of cancers. However, there are no studies regarding the anticancer effects of chrysophanol against the malignant meningioma of optic nerve. In this review, the potential of chrysophanol in the treatment of malignant ­meningioma of optic nerve was explored by evaluating its anticancer activity against the malignant meningioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It has reported that chrysophanol has an anti-tumor role in the cell proliferation of lung cancer via mediating ROS/HIF-1a/VEGF signaling cascade [ 19 ]; additionally, it also suppresses cell growth, migration, and reactive oxygen species generation in oral cancer cell lines [ 20 ]. Moreover, it induces apoptosis of malignant optic nerve meningioma cells via inducing the caspase activation and targeting the MAPKs signaling cascade [ 21 ]. Similarly, our results in a menangioma cell type suggest that chrysophanol suppresses the proliferation of tumor cells while promoting their apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has reported that chrysophanol has an anti-tumor role in the cell proliferation of lung cancer via mediating ROS/HIF-1a/VEGF signaling cascade [ 19 ]; additionally, it also suppresses cell growth, migration, and reactive oxygen species generation in oral cancer cell lines [ 20 ]. Moreover, it induces apoptosis of malignant optic nerve meningioma cells via inducing the caspase activation and targeting the MAPKs signaling cascade [ 21 ]. Similarly, our results in a menangioma cell type suggest that chrysophanol suppresses the proliferation of tumor cells while promoting their apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was detected via concurrent staining with annexin V-CF647 and 7-aminoactinomycin D (7-AAD) using a commercial kit (FCCH100108, FlowCellect Õ annexin V red kit; Sigma-Aldrich). 18 ENCCs were aliquoted as 1 Â 10 6 cells/100 mL into FACS tubes. The cells were washed twice, centrifuged, and pelleted.…”
Section: Flow Cytometric Analysis Of Cell Cycle and Apoptosis Of Enccsmentioning
confidence: 99%
“…The detection of phosphatidylserine using fluorochrome-tagged anticoagulant protein annexin V enabled precise estimation of apoptotic incidence. 18 Early apoptotic cells bind annexin V but exclude 7-AAD (annexin V þ 7-AAD À ). 18 In this study, compared to that in the controls (6.62 AE 3.78% vs 6.69 AE 3.54%, P > .05), PTU did not change the Figure 3.…”
Section: Ptu Reduced the Mitotic Activity Of Enccsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the pharmacological properties of chrysophanol have been researched; for example, resistant effects relative to inflammatory diseases, diabetes, bacterial, oxidation, ulcer, and cancer have been confirmed [ 31 , 32 ]. In addition, chrysophanol has shown potent anti-cancer effects on some cancers, such as liver, colon, and ovarian cancers [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%